2022
DOI: 10.3389/fcell.2022.994001
|View full text |Cite
|
Sign up to set email alerts
|

A rapid, non-invasive method for fatigue detection based on voice information

Abstract: Fatigue results from a series of physiological and psychological changes due to continuous energy consumption. It can affect the physiological states of operators, thereby reducing their labor capacity. Fatigue can also reduce efficiency and, in serious cases, cause severe accidents. In addition, it can trigger pathological-related changes. By establishing appropriate methods to closely monitor the fatigue status of personnel and relieve the fatigue on time, operation-related injuries can be reduced. Existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…Additionally, in this study, similar to the studies reported in [23], [37], and [70], the fatigue scale was introduced as a label value for model learning. Previous authors divided the test values of the scale into intervals to form fatigue and wakefulness intervals before inputting this information into their proposed models.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Additionally, in this study, similar to the studies reported in [23], [37], and [70], the fatigue scale was introduced as a label value for model learning. Previous authors divided the test values of the scale into intervals to form fatigue and wakefulness intervals before inputting this information into their proposed models.…”
Section: Discussionmentioning
confidence: 97%
“…Shen et al [36] proposed a high-precision feature extraction network to detect controller fatigue states using improved deep learning techniques. Gao et al [37] developed a rapid and non-invasive method to assess the degree of fatigue based on connections between voice features and the level of fatigue as determined by the SSS. Their work highlighted that vocal characteristics could also reflect the level of fatigue, exhibiting strong correlations with the scale test values.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The vitality section of the SF-36 questionnaire captures the energy and fatigue aspects of health [1]. Fatigue can refer to a variety of conditions such as sleep fatigue [2], work fatigue [3,4,5] and COVID-19 fatigue [6,7]. According to Ware et al [1], the vitality part of the questionnaire was added to capture "differences in subjective well-being".…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no direct research using audio to detect fatigue based on the SF-36 questionnaire has been done so far. In the area of sleep fatigue detection, the authors of [2] col-lected data from 15 participants and a Support Vector Machine (SVM) was trained on common audio features such as F0, Mel-Frequency Cepstral Coefficients (MFCCs), and loudness. Similarly, for work fatigue detection Krajewski et al [3] collected data from 12 participants and common audio features were used to train an ensemble of machine learning models such as a linear SVM, logistic regression, decision trees, and multi-layer perceptrons.…”
Section: Introductionmentioning
confidence: 99%